What drives visitor economy crowdfunding? The effect of digital storytelling on unified theory of acceptance and use of technology. (April 2020) - Kim, Myung Ja; Hall, C. Michael
Abstract: Digital storytelling is a key factor used by fundraisers to attract investors to crowdfunding projects. Despite the important role of digital storytelling in consumer persuasion, research on the effect of digital storytelling on consumer behavior is scarce in the visitor economy crowdfunding sector. The objective of this work is to create and verify a theoretically integrated research framework including three-dimensions of digital storytelling as a reflective second order factor (perceived esthetics, narrative structure, and self-reference) and concepts of unified theory of acceptance and use of technology (UTAUT) (performance expectancy, social influence, effort expectancy, facilitating condition, and intention). Results reveal that digital storytelling has highly significant effects on facilitating condition, performance expectancy, effort expectancy, and social influence in descending order. Investors' intention to crowdfund is also significantly affected by facilitating condition, performance expectancy, social influence, and effort expectancy in descending order, offering significant theoretical and managerial implications in leisure and tourism. Highlights: Crowdfunding is an increasingly significant source of capital in the visitor economy. Digital storytelling is an emerging factor in tourism crowdfunding in the UTAUT. Digital storytelling plays a significant role in funders' intention to crowdfund. Perceived esthetics is closely related to digital storytelling in crowdfunding. Facilitating condition has the most important role in crowdfunding digital storytelling.